Claims in surfing: The influence of emotional postperformance expressions on performance evaluations - Furley, P.; Thrien, F.; Klinge, J.; Dörr, J. (Journal of Sport & Exercise Psychology, 2020)
The goal of the present research was to investigate whether claims (postperformance nonverbal emotional expressions) influence people in evaluating performance during surf contests. To test this research question, the authors sampled videos from professional surf contests and asked laypeople (Experiment 1; N = 110) and surf judges (Experiment 2; N = 41) to evaluate the performance in 2 online experiments. A subset of the surfing performances showed surfers displaying postperformance emotional expressions (claims), while another subset showed the same performances without the claims (nonverbal emotional expressions). Both experiments provided evidence that both laypeople and surf judges were biased by claims in judging surfing performances, with claims better than the performances without claims. The findings are in line with social-cognitive models emphasizing the socioconsequences of emotion expressions. The authors discuss the implications of the findings for sport competitions that rely on judging sport performance.